Molecular Characterization of a Novel Begomovirus Infecting Malva (Gaya guerkeana K. Schum.) - Ferro, Mayra Machado de Medeiros; Tenório, Arthur Alencar Raposo; Silva, Sarah Jacqueline Cavalcanti da; Silva, Janaíne Rossane Araújo; Ramos-Sobrinho, Roberto; Lima, Gaus Silvestre de Andrade; Assunção, Iraildes Pereira (Comunicata Scientiae, 2018)
The genus Begomovirus (family Geminirvidae) comprises circular single-stranded DNA viruses that infect both cultivated and non-cultivated hosts, being transmitted by the insect vector Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). This study aimed to conduct the molecular characterization of a novel begomovirus infecting the non-cultivated plant Gaya guerkeana K. Schum. (Malvaceae). A leaf sample of G. guerkeana was collected in the State of Pernambuco, Brazil, in 2010. Viral genomic components were amplified via RCA, cloned, and commercially sequenced. The full-length DNA-A sequence was used for phylogenetic analysis and pairwise comparisons with other previously reported begomoviruses. The begomovirus DNA-A from G. guerkeana was most closely related to the Sida mottle Alagoas virus (SiMoAV, JX871386), having 84.8% nucleotide identity. Using the ≥ 91% identity criteria for DNA-A established by the Geminivirus Study Group of the International Committee on Taxonomy of Viruses, this isolate was considered a putative new begomovirus species, and the name Gaya yellow mosaic virus (GaYMV) is suggested. The GaYMV isolate grouped with SiMoAV and other begomoviruses infecting Sida spp. from the State of Alagoas, Brazil. This is the first report of a begomovirus infecting G. guerkeana, indicating that this non-cultivated plant can act as a reservoir/source of begomoviruses.